Strictly Endogenous Growth with Non-renewable Resources Implies an Unbounded Growth Rate - Christian Groth (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
Conventional endogenous growth theory relies on the assumption of constant returns to broad capital. As Solow pointed out, the strength of this assumption is revealed by recognizing that even the slightest touch of increasing returns creates explosive growth: infinite output in finite time! But Solows observation ignored natural resources. What happens if non-renewable resources enter the growth engine? In this case (strictly) endogenous growth requires the technology to be such that there is no upper bound on the sustainable per capita growth rate.
Keywords: O4; Q3; 330; endogenous growth; semi-endogenous growth; non-renewable resources; knife-edge; Neue Wachstumstheorie; Erschöpfbare Ressourcen; Theorie